Die Mar̈kte fur̈ Getreide, Ol̈saaten und Kartoffeln - Friedrich Uhlmann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Agricultural Markets at the Turn of 2001/2002: 2 Cereals Production 2001World cereals production in 2001 levelled around the 2000 crop. Minor dents in wheat and rice production contrasted with higher output of coarse grains. World wheat prices strength-ened.Reduced plantings and lower average yields let the EU wheat crop fall by 12 per cent from the previous year. The fall was yet less than expected with regard to adverse weather in some important wheat growing areas. The second reduction of the EU intervention price through CAP reform (Agenda 2000) became effective by the beginning of the 2001/02 marketing year. Consid-erations by the European Commission about an end of rye inter-vention purchases began to worry arable farmers in Northeast Germany where rye is the main grain crop.
Keywords: 330